Building Capacity in VA to Provide Emergency Gynecology Services for Women. Issue 4 (April 2015) - Cordasco, Kristina M.; Huynh, Alexis K.; Zephyrin, Laurie; Hamilton, Alison B.; Lau-Herzberg, Amy E.; Kessler, Chad S.; Yano, Elizabeth M.
Abstract : Background: Visits to Veterans Administration (VA) emergency departments (EDs) are increasingly being made by women. A 2011 national inventory of VA emergency services for women revealed that many EDs have gaps in their resources and processes for gynecologic emergency care. Objectives: To guide VA in addressing these gaps, we sought to understand factors acting as facilitators and/or barriers to improving VA ED capacity for, and quality of, emergency gynecology care. Research Design: Semistructured interviews with VA emergency and women's health key informants. Subjects: ED directors/providers (n=14), ED nurse managers (n=13), and Women Veteran Program Managers (n=13) in 13 VA facilities. Results: Leadership, staff, space, demand, funding, policies, and community were noted as important factors influencing VA EDs building capacity and improving emergency gynecologic care for women Veterans. These factors are intertwined and cross multiple organizational levels so that each ED's capacity is a reflection not only of its own factors, but also those of its local medical center and non-VA community context as well as VA regional and national trends and policies. Conclusions: Policies and quality improvement initiatives aimed at building VA's emergency gynecologic services for women need to be multifactorial and aimed at multiple organizational levels. Policies need to be flexible to account for wide variations across EDs and their medical center and community contexts. Approaches that build and encourage local leadership engagement, such as evidence-based quality improvement methodology, are likely to be most effective.